2021
DOI: 10.1080/23802359.2021.1960215
|View full text |Cite
|
Sign up to set email alerts
|

Complete maternal mitochondrial genome of the freshwater mussel Cuneopsis celtiformis (Bivalvia: Unionidae)

Abstract: The genus Cuneopsis Simpson, 1900 comprises seven valid species, and Cuneopsis celtiformis (Heude, 1874) is the type species of this genus. Previous phylogenetic studies using complete mitochondrial genomes showed that Cuneopsis was not monophyletic, but the result was hampered by incomplete species sampling and lack of the type species of this genus. In this study, we collected C. celtiformis fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although previous molecular studies have thrown some light on Cuneopsis classification, generic monophyly and inter-species relationships were weakly supported (Huang et al, 2019;Wu et al, 2018). With the expansion of taxa sampling (Lopes-Lima et al, 2020) and datasets (Dai et al, 2021;Wu et al, 2019), Cuneopsis was found to be non-monophyletic and still not well resolved with its allied genera (including Nodularia, Schistodesmus, and Inversiunio). Therefore, a conclusive assessment on Cuneopsis should include the type species C. celtiformis, together with comprehensive species sampling.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Although previous molecular studies have thrown some light on Cuneopsis classification, generic monophyly and inter-species relationships were weakly supported (Huang et al, 2019;Wu et al, 2018). With the expansion of taxa sampling (Lopes-Lima et al, 2020) and datasets (Dai et al, 2021;Wu et al, 2019), Cuneopsis was found to be non-monophyletic and still not well resolved with its allied genera (including Nodularia, Schistodesmus, and Inversiunio). Therefore, a conclusive assessment on Cuneopsis should include the type species C. celtiformis, together with comprehensive species sampling.…”
mentioning
confidence: 83%
“…As the F-type mitogenomes of Cuneopsis species have been successively determined, mitochondrial phylogenomics preliminarily the polyphyly of Cuneopsis, even though affinities among Cuneopsis s.l. and its allied genera lacked strong nodal support (Dai et al, 2021;Wu et al, 2019). In our present study, all currently recognized species of Cuneopsis, except C. kiangsiensis, are included and subjected to whole mitogenome sequencing.…”
Section: Molecular Datingmentioning
confidence: 99%
“…The genus is closely related to Cuneopsis Simpson, 1900, and Tchangsinaia Starobogatov, 1970. Cuneopsis sensu lato Simpson, 1900, which mainly includes species endemic to China (Wu et al., 2022), is polyphyletic in recent studies (Dai et al., 2021; Wu et al., 2019). Based on mitochondrial phylogenomic analyses, our previous research (Wu et al., 2022) has confirmed and categorized Cuneopsis s.l .…”
Section: Introductionmentioning
confidence: 99%